Funkcija kulture v čezmejnem sodelovanju v prostoru Alpe-Jadran - Valentin, Hellwig (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
THE FUNCTION OF CULTURE IN CROSS-BORDER COOPERATION IN THE ALPS-ADRIA REGION. The article focuses on the importance of cross-border cooperation for European integration processes. Cross-border cooperation at regional level is of decisive importance as to the longterm success of the European integration process. The author emphasizes the significance of the Alps-Adria Working Community, founded in 1978, for the integration in the East-Alpine area. Having gone through an extensive reformation process in 2006, the Working Community of 13 members is now well prepared for future tasks. The author further discusses the integrative potential of languages and cultures in the united Europe. Preservation of linguistic and cultural diversity is an important task, and all tendencies for centralization have to be withstood. Culture paves the way for cross-border cooperation, the Alps-Adria region being a good example. National communities are extremely important for this preservation and thus also for the integration of Europe. Protection and promotion of these communities are therefore an interest of foremost importance. National communities in cross-border cooperation are also an important initiator and bridge-building factor, and conflicts in this field have a negative impact on neighbouring relations. The author points at the elementary work, carried out in the Alps- Adria Working Community, concerning the status of national communities and their role in cross-border cooperation.
Keywords: kulturno sodelovanje; Alpe-Jadran; narodne skupnosti; čezmejno sodelovanje; evropska integracija